Elaboration Et Caractérisation Des Couches d’Oxyde de Cuivre Sur des Substrats d’Oxyde de Zinc par Bain Chimique - Allag, Noussiba (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2020)
The present work deals with the deposition of CuO thin films on substrates of zinc oxide by a simple and cheap technique such as chemical bath (CB). In first, a set of ZnO thin film was prepared using optimized spray pyrolysis conditions in order to devote the films for ions copper adsorption from aqueous solution.Two sources (zinc acetate and zinc chloride ) are considered as deposition parameters. LaCl3 7H2O was used with different rate of doping.The Structural, morphological and optical results confirm that the films are ZnO hexagonal wurtzite structure with a strong orientation along (002) with excellent optical properties. Further, the application of thin films as adsorbent was studied by Cu(II) adsorption from aqueous solution 0.2M. The obtained ZnO:La 1wt .% films are an effective adsorbent for removing Cu(II) with high adsorption capacity (87%). Thin films of copper oxide were obtained after annealing the ZnO:La substrates at temperature ranging between 200 - 350 °C. Structural, morphological, and optical characterizations were performed on the CuO films. The structural analysis of the later shows that the obtained films are polycrystalline, they exhibit a monoclinic structure. The preferential orientation is strongly related to the experimental parameters studies. From the optical characterization, it was inferred that the deposited films have suitable optoelectronic properties for the photovoltaic applications since they present a good absorption in the visible range . موضوع الرسالة يتناول تحضير ودراسة الشرائح الرقيقة أكسيد النحاس (CuO) باستعمال تقنية سهلة وبسيطة و التي تتمثل في تقنية الحمام الكيميائي ( (Bath Chemical BC. فى الجزء الاول من هذا العمل قمنا بتحضير سلسلة من العينات أكسيد الزنك (ZnO) و المحضرة بطريقة الرش الحراري ( (Spray pyrolysis SP بتغيير الشروط التجريبية من اجل إيجاد أفضل الشروط التي تؤدى إلى شرائح ذات خصائص جيدة حيث يمكن استعمالها في امتصاص أيونات النحاس في محلول الماء. الوسائط التي قمنا بدراستها كانت على التوالي : نسبة التطعيم و نوعية الملح الأولي . تؤكد نتائج الخصائص الهيكلية والمورفولوجية والضوئية أن أكسيد الزنك (ZnO) له بنية سداسية Wurtzite مع نمو تفضیلي قوي في الاتجاه (002) وكذلك جودة بلورية عالية مع خاصية بصرية ممتازة . علاوة على ذلك ، تمت دراسة تطبيق الشرائح الرقيقة كممتز بواسطة امتزاز(Cu II ) من المحلول المائي. إن ركيزة ZnO: La1wt.٪ عبارة عن ممتز فعال لإزالة (Cu II) بسعة امتصاص عالية. بعد تلدين امساند عند درجة حرارة تتراوح بين 200 إلى 350 درجة مئوية. حصلنا على شرائح رقيقة من أكسيد النحاس . تم إجراء ودراسة الخصائص البنيوية, المورفولوجية والضؤية على شرائح CuO . الخصائص البنيوية وضحت أن التركيب البلوري للشرائح كان ذو تركيبة أحادية (monoclinique)متعددة التبلور بينما الاتجاه البلوري المفضل يتعلق بشروط التحضير. من نتائج التوصيف الضوئي ، استنتجنا أن الشرائح المودعة لها خصائص الكتروضوئية مناسبة للتطبيقات الكهروضوئية لأنها تتميز بامتصاص جيد في النطاق المرئي
أطروحة دكتوراه تخصص طاقوية في العلوم التكنولوجيا
Keywords: Zinc, thin films, XRD, UV-Visible, spray pyrolysis, oxide, copper, heavy metal, chemical bath.; زنك ، شريحة رقيقة ، انعراج الأشعة السينية ، مرئي للأشعة فوق البنفسجية ، الرش الحراري ، أكسيد ، نحاس ، معدن ثقيل ، حمام كيميائي